New modal gravity container by monorail/cable car - Saito, Jorge (Revista Hipótese, 2016)
The project seeks to implement a new system for transporting containers by gravity monorail/cable car in the region of Itapetininga /São Miguel Arcanjo through the construction of a Dry Port in the mountain region, connected by Cable Car to Sete Barras. It will need to win an unevenness of 760 meters towards the Port of Iguape transforming it into a Hub Port. It appears that there is already in place a state road SP 139, known locally as Serra da Macaca Road. This road would have to deployment without the need to build an access road to the implementation of the system. The modal cable car would use the physics principle of kinetic and potential energy, the container that falls, pulls the rising and so has a low power consumption, thus being able to use solar or wind energy. It is an environmentally friendly project, not causing air pollution, either producing noise. In addition, this project would, if implemented, the withdrawal of the trucks transporting containers of metropolitan region of São Paulo, contributing to the improvement of the chaotic traffic of this region. This project can be deployed in any place in the Serra do Mar mainly in São Paulo and Parana State.
Keywords: Monorail; Dry Port; Hub Port